HAP and VAP after Guidelines - Wicky, Paul-Henri; Martin-Loeches, Ignacio; Timsit, Jean-François (Seminars in Respiratory and Critical Care Medicine, 2022)
Nosocomial pneumonia is associated with worsened prognosis when diagnosed in intensive care unit (ICU), ranging from 12 to 48% mortality. The incidence rate of ventilation-acquired pneumonia tends to decrease below 15/1,000 intubation-day. Still, international guidelines are heterogeneous about diagnostic criteria because of inaccuracy of available methods. New entities have thus emerged concerning lower respiratory tract infection, namely ventilation-acquired tracheobronchitis (VAT), or ICU-acquired pneumonia (ICUAP), eventually requiring invasive ventilation (v-ICUAP), according to the type of ventilation support. The potential discrepancy with non-invasive methods could finally lead to underdiagnosis in almost two-thirds of non-intubated patients. Delayed diagnostic could explain in part the 2-fold increase in mortality of penumonia when invasive ventilation is initiated. Here we discuss the rationale underlying this new classification.Many situations can lead to misdiagnosis, even more when the invasive mechanical ventilation is initiated. The chest radiography lacks sntivity and specificity for diagnosing pneumonia. The place of chest computed tomography and lung ultrasonography for routine diagnostic of new plumonary infiltrate remain to be evaluated.Microbiological methods used to confirm the diagnostic can be heterogeneous. The development of molecular diagnostic tools may improve the adequacy of antimicrobial therapies of ventilated patients with pneumonia, but we need to further assess its impact in non-ventilated pneumonia.In this review we introduce distinction between hospital-acquired pneumonia according to the localization in the hospital and the oxygenation/ventilation mode. A clarification of definition is the first step to develop more accurate diagnostic strategies and to improve the patients' prognosis.
Keywords: hospital-acquired pneumonia; ventilator-associated pneumonia; ventilator-associated tracheobronchitis; ventilator-associated lower respiratory tract infection